Characterization of Sigma 1 Receptor Antagonist CM-304 and Its Analog, AZ-66: Novel Therapeutics Against Allodynia and Induced Pain - Cirino, Thomas J.; Eans, Shainnel O.; Medina, Jessica M.; Wilson, Lisa L.; Mottinelli, Marco; Intagliata, Sebastiano; McCurdy, Christopher R.; McLaughlin, Jay P. (Frontiers in Pharmacology, 2019)
Sigma-1 receptors (S1R) and sigma-2 receptors (S2R) may modulate nociception without the liabilities of opioids, offering a promising therapeutic target to treat pain. The purpose of this study was to investigate the in vivo analgesic and anti-allodynic activity of two novel sigma receptor antagonists, the S1R-selective CM-304 and its analog the non-selective S1R/S2R antagonist AZ-66. Inhibition of thermal, and induced chemical or inflammatory pain, as well as the allodynia resulting from chronic nerve constriction injury (CCI) and cisplatin exposure as models of neuropathic pain were assessed in male mice. Both sigma receptor antagonists dose-dependently (10-45 mg/kg, i.p.) reduced allodynia in the CCI and cisplatin neuropathic pain models equivalent at the higher dose to the effect of the control analgesic gabapentin (50 mg/kg, i.p.), although AZ-66 demonstrated a much longer duration of action. Both CM-304 and AZ-66 produced antinociception in the writhing test (0.48 (0.09-1.82) and 2.31 (1.02-4.81) mg/kg, i.p., respectively) equivalent to morphine (1.75 (0.31-7.55) mg/kg, i.p.). Likewise, pretreatment (i.p.) with either sigma-receptor antagonist dose-dependently produced antinociception in the formalin paw assay of inflammatory pain. However, CM-304 (17.5 (12.7-25.2) mg/kg, i.p.) and AZ-66 (11.6 (8.29-15.6) mg/kg, i.p.) were less efficacious than morphine (3.87 (2.85-5.18) mg/kg, i.p.) in the 55oC warm-water tail-withdrawal assay. While AZ-66 exhibited modest sedative effects in a rotarod assay and conditioned place aversion, CM-304 did not produce significant effects in the place conditioning assay. Overall, these results demonstrate the S1R selective antagonist CM-304 produces antinociception and anti-allodynia with fewer liabilities than established therapeutics, supporting the use of sigma-1 receptor antagonists as potential treatments for chronic pain.